Misconceptions about variables at the K-12 level - Žanko, Žana; Mladenović, Monika; Boljat, Ivica (Education and information technologies, 2019)
There are known misconceptions about variables which are mostly the same since the first studies since more than 30 years ago. Consciousness about the misconceptions in programming can be crucial for teaching and learning programming for novices because, if we are aware of them, maybe we can minimise or even prevent them. Researchers mostly conducted researches on an undergraduate or graduate level. There is a lack of studies about variable misconceptions at the K-12 level. Do K-12 students have the same misconceptions as undergraduates? Does the use of different programming languages affect misconceptions? We conducted the pilot study in the school setting among 127 elementary 5th and 6th-grade students. Students were learning to programme in text-based programming languages Logo, and Python with graphical (Logo) and procedural (Python) approaches. In this paper, we present the results of the research in which we aim to give answers to the questions posed above.